Does COVID-19 Policy Affect Initiation and Duration of Exclusive Breastfeeding? A Single-center Retrospective Study - Al Shahrani AS (Dove Medical Press, 2022)
Abeer Salem Al Shahrani Department of Clinical Sciences, College of Medicine, Princess Nourah Bint Abdulrahman University, Riyadh, Saudi ArabiaCorrespondence: Abeer Salem Al ShahraniDepartment of Clinical Sciences, College of Medicine, Princess Nourah bint Abdulrahman University, PO Box 84428, Riyadh 11671, Saudi Arabia, Tel +9660118239031Email asalshahran@pnu.edu.saPurpose: It assessed the effect of a COVID-19 policy that involved maternal-neonatal separation on early initiation and duration of exclusive breastfeeding (EBF) at two weeks, three, and six months postpartum during the peak of the COVID-19 pandemic in 2020.Patients and Methods: This retrospective study included consecutive mother-newborn dyads with deliveries between mid-March and the end of December 2020 who agreed to participate and were eligible according to the following criteria: full-term pregnancy, singleton birth, and healthy newborn. Participants were called at least twice during the study period to inquire about exclusive breastfeeding status at two weeks, three, and six months postpartum. Multivariate logistic regression analysis was carried out to identify associated factors with EBF.Results: A total of 454 eligible mother-infant dyads were included. Mean maternal age (in years), gestational age (in weeks), birth weight (in kilograms), and 5-min Apgar score was, respectively, 32± 5.4 years, 39± 1.3 weeks, 3.1± 0.42 kg, and 9.24± 0.6. Most of the mothers (86.1%) had no known chronic diseases and had a normal spontaneous vaginal delivery (NSVD, 91.4%). Approximately 44.7% of the sample initiated breastfeeding either directly or with expressed breastmilk during their hospital stay. Prevalence of EBF during the first two weeks, three, and six months postpartum was, respectively, 30%, 19.8%, and 31.7%. EBF was associated with birth weight, hospital breastfeeding and EIBF at early postpartum period, while EBF at six months was associated with parity and method of delivery.Conclusion: During the peak of the COVID-19 pandemic, the prevalence of breastfeeding initiation and EBF in the first six months postpartum were low among Saudi mothers. However, multicenter, prospective, cohort studies with adjustment for known confounding factors are required to explore the impact of infection control policies on breastfeeding. Meanwhile, these policies should support early and safe breastfeeding practices, especially with new and evolving information regarding the current pandemic.Keywords: COVID-19, pandemic, breastfeeding, exclusive breastfeeding, policy